2011
DOI: 10.3855/jidc.1199
|View full text |Cite
|
Sign up to set email alerts
|

Potency of detergents in enhancing Schistosoma mansoni tegumental antigens

Abstract: Introduction: Vaccine strategies represent an essential component for the future control of schistosomiasis. This work aimed to evaluate the role of detergents for potentiating the effect of Schistosoma mansoni tegumental antigens (TA) against challenge infection. Methodology: Two detergents; Triton X-100 (TX-100) and sodium dodecyl sulfate (SDS), were selected for extraction of tegumental proteins. Mice were vaccinated with two doses of each preparation (100 μg protein) at time intervals 15 days before infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The thickness of the ileal muscular layer was slightly but significantly reduced by 10.52%. Reduction of granuloma number and/or size has been previously reported by others authors after treating S. mansoni -infected mice with curcumin [ 13 ], Zingiber officinale rhizomes [ 33 ], berberine [ 4 ], Ceratonia siliqua pod [ 8 ], selenium nanoparticles [ 5 ] or vaccination of mice with the tegumental antigen of S. mansoni adult worms prior to infection [ 34 ]. The formation and the development of hepatic granuloma are intimately linked to inflammatory cells infiltration in the liver.…”
Section: Discussionmentioning
confidence: 90%
“…The thickness of the ileal muscular layer was slightly but significantly reduced by 10.52%. Reduction of granuloma number and/or size has been previously reported by others authors after treating S. mansoni -infected mice with curcumin [ 13 ], Zingiber officinale rhizomes [ 33 ], berberine [ 4 ], Ceratonia siliqua pod [ 8 ], selenium nanoparticles [ 5 ] or vaccination of mice with the tegumental antigen of S. mansoni adult worms prior to infection [ 34 ]. The formation and the development of hepatic granuloma are intimately linked to inflammatory cells infiltration in the liver.…”
Section: Discussionmentioning
confidence: 90%
“…Results from Table 1 revealed that S. mansoni -infected mice exhibited significant growth retardation and hepatosplenomegaly. Enlargement of the liver is thought to be due to eggs deposition in the hepatic tissue and enlargement of the spleen is due to passive congestion of blood flow and reticuloendothelial hyperplasia 35, 36. The mechanism behind hepatosplenomegaly is probably related to immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Schistosoma eggs are known to produce several tissue-reactive substances including lipids, antigens, and enzymes, as well as reticuloendothelial cell infiltration and fibro granulomatous tissue, which lead to liver enlargement. 33 Moreover, the increase in the relative liver weight may be attributed to both egg deposition by worms and several metabolites released by S. mansoni , which affect the host hepatic tissue. 34…”
Section: Discussionmentioning
confidence: 99%